A systematic review of indicators for evaluating the effectiveness of digital public services - Pedrosa, Glauco Vitor (2020)
Effectiveness is a key feature of good governance, as the public sector must make the best use of resources to comply with the needs of the population. Several indicators can be analyzed to evaluate the effectiveness of a service. This study analyzes theoretical references and presents a systematic research of indicators to assess the effectiveness of digital public services in the perspective of the user. First, a literature review was carried out to identify the most common indicators employed to evaluate effectiveness in the public sector; then, the perception of academics and professionals regarding digital government was assessed to analyze the relevance of these indicators. As a result, two groups of indicators were found: technical factors based on service quality and usefulness of the service. This work contributes to enrich the discussion on how to create an effective model to evaluate the effectiveness of public services to guarantee quality standards and comply with the expectations of users.